2020
DOI: 10.1080/13876988.2020.1813031
|View full text |Cite
|
Sign up to set email alerts
|

Singing Together or Apart? Comparing Policy Agenda Dynamics within International Organizations

Abstract: Are there substantial differences between the issues an IO's decision-making body agrees upon and the issues the organization's administrative body is dealing with in practice? Or are member states and the administration singing (to) the same tune? To tackle these questions, this article explores agenda congruence in three single-purpose organizations using methods of quantitative text analysis. The explorative empirical analysis shows that both change dynamics and agenda congruence exhibit substantial variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…IPAs are not always servants of their member states' power, but they are distinct authorities that carefully defend their legitimacy. Scholars analyzing IOs' behavior should thus differentiate between member states (and their governing bodies) and IPAs as actors in their own right (see also Bayerlein et al 2020;Goritz et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…IPAs are not always servants of their member states' power, but they are distinct authorities that carefully defend their legitimacy. Scholars analyzing IOs' behavior should thus differentiate between member states (and their governing bodies) and IPAs as actors in their own right (see also Bayerlein et al 2020;Goritz et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…2 Since the codebook is based on Western government's functions, however, using it directly for analyzing Chinese textual data may introduce coding biases. To address this, we adopted an "inductive" approach by combining topic modeling with text coding for more contextually relevant analysis (Bayerlein et al, 2022). The reason for first using topic modeling instead of direct coding is that we cannot pre-determine the specific policy topics contained in the textual data and the relationships among them.…”
Section: Data Collectionmentioning
confidence: 99%
“…By treating both sides seriously, we should learn more about how these actors interact with each other and what dynamics drive their behaviour both within and between these actors. A few very recent studies have already demonstrated the benefits of such perspective: showed how the lack of synchronized action between member states and IO administrations can lead to significant institutional failures; showed how member states' actions and IPAs' perception thereof contribute to the emergence of informal behaviour patterns in IOs; a study by Bayerlein et al (2020a) showed that the congruence between member states' and IPAs' policy agendas may vary depending on the extent to which member states delegate formal authority to IPAs as well as the extent to which IPAs' administrative cultures foster independent agenda developments. Hence, if such relational dynamics remain ignored, P-A approaches cannot unleash their explanatory power.…”
Section: First P-a Studies Of Delegation To Ios Often Lack Clear Defi...mentioning
confidence: 99%